Radiosensitivity of glioblastoma multiforme and astrocytic cell lines in cell signalling aspects - Çalık Kocatürk, Duygu; Ozdil, Berrin; Adalı, Yasemin; Hoca, Sinan; Kamer, Serra; Öktem, Gülperi; Uysal, Ayşegül; Aktuğ, Hüseyin (The European Research Journal, 2023)
Objectives: The aim of this study is to investigate the radiosensitivity of Glioblastoma multiforme (GBM; U87 MG) and astrocyte (SVG p12) cell lines in vitro through the signalling pathways. Methods: GBM and astrocytes were treated with 2, 4, 6, and 8 gray of ionized radiation, followed by a clonogenic assay. The effective dose of radiation was determined as 2 gray. Immunofluorescence technics selected to analyse the macrophage migration inhibiting factor (MIF), nuclear factor of activated T-cells cytoplasmic 2 (NFATc2), osteopontin (OPN), mammalian target of rapamycin (mTOR) and stage-specific embryonic antigen-1 (SSEA-1). Additionally, p53 and cell cycle assays were performed. Results: On day 1, astrocytes showed decreased expression of MIF, OPN and mTOR and increased expression of SSEA-1 in the test group after 2 gray radiation. GBM showed decreased expression of p53 and mTOR, but increased expression of NFATc2. The results of MIF expression were found higher in GBM compared to astrocytes on day 1. Interestingly, on day 12, increased expression of SSEA-1, OPN and p53 were observed in both cell lines’ test groups. Further analysis showed that all control groups of GBM and astrocytes were significantly accumulated in the S phase. After radiotherapy application, percentage of GBM in G0/G1 phases and especially in G2/M phases increased; conversely, in the S phase it decreased. Moreover, percentage of astrocytes increased in the S phase and decreased in G0/G1 phases and in G2/M phases. Conclusions: This combination of findings suggests that as a result of the radiotherapy effect, GBM started to accumulate on check points. The central question in this study focused on changes in molecular protein expression in cancer cells after radiotherapy, particularly key signalling pathways of tumorigenesis and a new possible point of view for treating such diseases.